The Dilemmas of Giving: The Heart of Paradox - Hampden-Turner, Charles (Institutional Knowledge at Singapore Management University, 2008)
In their attempts to ‘do-good’ and alleviate the pains of the less fortunate, the impoverished and the disadvantaged, foundations and charitable bodies face common dilemmas. Professor Charles Hampden-Turner and Professor Tan Teng Kee explore.